Di-tert-butyl N,N `-(octahydropentalene-2,5-diyl) dicarbamate - Kendhale, Amol M.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Acta Crystallographica Section E-Structure Reports Online, 2008)
In the molecule of the title compound, C18H32N2O4, the central bicyclo[3.3.0] octane (octahydropentalene) has a rigid ring junction. Both rings of the bicyclo[3.3.0] octane unit adopt an envelope conformation, and the flexible tert-butylcarbamoyl side chains each have an extended conformation. Such a constrained bicyclo[3.3.0] octane aliphatic template is of interest with respect to the design of novel self-assembling motifs. Molecules related by c-glide symmetry are linked via intermolecular N-H center dot center dot center dot O hydrogen bonds, forming a two-dimensional layer structure. Neighboring layers are weakly associated along the a axis due to the close approach of the tert-butylcarbamoyl groups (2.55 angstrom).